A simplified method for monomeric carbohydrate analysis of corn stover biomass. Issue 3 (May 2014) - Mourtzinis, Spyridon; Arriaga, Francisco J.; Bransby, David; Balkcom, Kipling S.
Abstract Constituent determination of biomass for theoretical ethanol yield (TEY) estimation requires the removal of nonstructural carbohydrates prior to analysis to prevent interference with the analytical procedure. According to the accepted US Department of Energy‐National Renewable Energy Laboratory (NREL) method, biomass extractives in corn stover should be removed by a two‐step extraction process. Alternatively, Neutral Detergent Fiber method (NDF) is a fast and cost‐effective method used to determine structural carbohydrates of forage biomass. The objective of this study was to determine whether the NDF method can be used as an alternative to the NREL extraction procedure for corn (Zea mays L.) stover biomass. Arabinan content varied between the two methods. However, glucan, xylan, and TEYs were not statistically different. Furthermore, the average TEYs per unit of mass and unit of area varied by 2.0 and 1.9%, respectively. Additionally, the NDF extraction procedure was faster and less expensive than the NREL procedure.